Prevalence of Ophthalmia Neonatorum in Calabar, South-South Nigeria: A 3-Year Review - Sunny Oteikwu Ochigbo; Affiong Ibanga; Ikechukwu Uzomba (Mashhad University of Medical Sciences, 2016)
Background: Ophthalmia neonatorum (ON) also known as neonatal conjunctivitis is inflammation of the conjunctiva caused by aseptic or septic factors. It commonly affects newborns usually within the first month of life. This study aimed to determine the prevalence and socio-demographic characteristics of ON in Calabar, Nigeria. Methods: We retrieved all the clinical case notes with diagnosis of ON from the Neonatal Unit of University of Calabar Teaching Hospital (UCTH), Calabar, Nigeria, during 1st January 2012-31st December, 2014. The extracted information included age at presentation, gender, socio-demographic characteristics, conducted investigations, treatment, and outcome. Data was analyzed using SPSS, version 20. Results: Out of a total of 3198 admissions, 34 (1.1%) had ON, most of whom were females (58.8%), and 21(61.8%) of the cases were admitted to the out-born neonatal unit. Eye swabs were taken from only 18 (52.9%) cases for microscopy, culture, and sensitivity prior to antibiotics initiation, from which no organism was isolated. Parents of the studied neonates were mainly from low and middle socioeconomic classes. Conclusion: Determination of organisms responsible for ON is of paramount importance. Therefore, hospital delivery and maternal education on this condition should be considered as priorities. In addition, clinicians are suggested to take regular eye swabs for microbiological investigations prior to initiation of treatment.